2017
DOI: 10.1038/s41598-017-07554-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficient functional neutralization of lethal peptide toxins in vivo by oligonucleotides

Abstract: Medical means to save the life of human patients affected by drug abuse, envenomation or critical poisoning are currently limited. While the compounds at risks are most often well identified, particularly for bioterrorism, chemical intervention to counteract the toxic effects of the ingested/injected compound(s) is restricted to the use of antibodies. Herein, we illustrate that DNA aptamers, targeted to block the pharmacophore of a poisonous compound, represent a fast-acting and reliable method of neutralizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 38 publications
3
33
0
Order By: Relevance
“…Although the main work was performed on a cone snail toxin, and not a snake toxin, another approach to developing novel compounds for snakebite envenoming therapy focuses on the use of oligonucleotides. In 2017, El-Aziz and colleagues published an article arguing for favourable characteristics of oligonucleotides including low immunogenicity, small size, thermal stability, biocompatibility, and standardised production methods [38]. Oligonucleotides are devoid of many of the drawbacks associated with antibody production by immunisation (e.g.…”
Section: Oligonucleotides and Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the main work was performed on a cone snail toxin, and not a snake toxin, another approach to developing novel compounds for snakebite envenoming therapy focuses on the use of oligonucleotides. In 2017, El-Aziz and colleagues published an article arguing for favourable characteristics of oligonucleotides including low immunogenicity, small size, thermal stability, biocompatibility, and standardised production methods [38]. Oligonucleotides are devoid of many of the drawbacks associated with antibody production by immunisation (e.g.…”
Section: Oligonucleotides and Antibodiesmentioning
confidence: 99%
“…The ED50 against lethality for the oligonucleotide was determined to be 0.18 µg/g mouse bodyweight when administered intraperitoneally, and 0.22 µg/g mouse bodyweight when administered subcutaneously. As the oligonucleotide was unable to inhibit a different blocker (waglerin) of the muscle nicotinic acetylcholine receptor targeted by the conotoxin, the oligonucleotide was assumed to be specific for αC-conotoxin PrXa [38]. Another benefit of working with oligonucleotides in the lab setting includes the low cost of small scale synthesis for R&D purposes, which makes it easy for researchers to quickly evaluate a large range of molecules at limited cost.…”
Section: Oligonucleotides and Antibodiesmentioning
confidence: 99%
“…Although the main work was performed on a cone snail toxin, and not a snake toxin, another approach to developing novel compounds for snakebite envenoming therapy focuses on the use of oligonucleotide-based aptamers, which have found various applications, including in therapeutics [ 47 ]. In 2017, El-Aziz and colleagues published an article arguing for favourable characteristics of oligonucleotides, including low immunogenicity, small size, thermal stability, biocompatibility, and standardised production methods [ 48 ]. Oligonucleotides are devoid of many of the drawbacks associated with antibody production by immunisation (e.g., use of production animals, long production time, poor immunogenicity of many smaller toxins, and cost of production) and with the treatment itself (e.g., immunogenicity of animal-derived antibodies, limited shelf-life, need for refrigeration, and potential lack of specificity).…”
Section: Oligonucleotides and Antibodiesmentioning
confidence: 99%
“…The ED 50 against lethality for the oligonucleotide was determined to be 0.18 µg/g mouse bodyweight when administered intraperitoneally, and 0.22 µg/g mouse bodyweight when administered subcutaneously. As the oligonucleotide was unable to inhibit a different blocker (waglerin) of the muscle nicotinic acetylcholine receptor targeted by the conotoxin, the oligonucleotide was assumed to be specific for αC-conotoxin PrXa [ 48 ]. Another benefit of working with oligonucleotides in the lab setting includes the low cost of small-scale synthesis for research and development (R&D) purposes, which makes it easy for researchers to quickly evaluate a large range of molecules at limited cost.…”
Section: Oligonucleotides and Antibodiesmentioning
confidence: 99%
“…In addition, a summary of the clinically most important toxin families in snake, scorpion, and spider venoms is presented, as well as how complementary biochemical, bioinformatic, and omics tools can be exploited to design cutting-edge immunization protocols. Novel approaches in the therapy of envenomings, such as the development of toxin inhibitors based on aptamers, small molecules, or recombinant antibodies (or fragments thereof) of human or camelid origin are beyond the scope of this review, and can be found elsewhere [ 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%